2014
DOI: 10.1007/s00464-013-3391-8
|View full text |Cite
|
Sign up to set email alerts
|

Elective laparoscopic cholecystectomy for symptomatic uncomplicated gallstone disease: do the symptoms disappear?

Abstract: According to our data, more than one-third of patients with symptomatic uncomplicated gallstone disease experienced persistent symptoms after elective LC. Patients with mild preoperative symptoms seemed to have more recurrences than those with severe symptoms, although the difference was not statistically significant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 14 publications
2
7
0
1
Order By: Relevance
“…We reported a high overall satisfaction rate (96%) following cholecystectomy in respondents (with 71% reporting being “ very satisfied ”), which is comparable to rates ≥88% reported in other studies of cholecystectomy patients [10, 14–16]. In a high‐volume centre such as ours [17], this surgical experience can have substantial benefits in surgical outcomes, particularly for high‐risk patients.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…We reported a high overall satisfaction rate (96%) following cholecystectomy in respondents (with 71% reporting being “ very satisfied ”), which is comparable to rates ≥88% reported in other studies of cholecystectomy patients [10, 14–16]. In a high‐volume centre such as ours [17], this surgical experience can have substantial benefits in surgical outcomes, particularly for high‐risk patients.…”
Section: Discussionsupporting
confidence: 81%
“…However, this was not observed within our sample (Table 2), which could be expected within a routinely day‐case procedure. Furthermore, few (15%) of patients reported recurrent symptoms compared to other studies reporting recurrence in up to 40% of patients [10, 30, 31]. However, as these studies involved longer periods of follow‐up, patients may yet develop symptoms in the future.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Three large studies showed similar proportions of persistent symptoms, viz. 37 [31], 40.4 [19], and 59.5% [32]. Previous literature suggests that if the preoperative assessment is standardized and other possible causes of abdominal symptoms are ruled out, the postoperative symptomatic outcome is significantly improved [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…A colelitíase é a doença mais prevalente da árvore biliar, responsável pela maior parte das cirurgias eletivas realizadas anualmente 1,2 . É caracterizada principalmente por queixas abdominais e tem como principal tratamento a colecistectomia videolaparoscópica 3,4 , atualmente recomendada precocemente na ausência de contraindicações com o objetivo de prevenir complicações relacionadas à doença e recorrência dos sintomas 5 .…”
Section: Introductionunclassified